THE EFFECT OF AN INSTRUCTIONAL PROGRAM BASED ON A RECIPROCAL TEACHING STRATEGY ON DEVELOPING JORDANIAN THIRD GRADE STUDENTS REFLECTIVE THINKING IN ARABIC LANGUAGE AND THEIR ATTITUDES TOWARD IT - Hadaib, Rasha Youssef; Talafha, Hamed Abdullah (Journal of Educational and Psychological Sciences, 2018)
This study aimed to investigate the effect of implementing an instructional program that is based on the reciprocal teaching strategy on developing Jordanian third grade students' reflective thinking in Arabic language subject and their relevant attitudes, by means of comparing this program to the conventional program of teaching.Sample of the study was chosen purposefully and consisted of (83) male and female students of third grade distributed in two classes. This sample was divided randomly into two groups: an experimental group that consisted of (43) students who studied according to the instructional program based on the reciprocal teaching strategy, and a control group that consisted of (40) students who studied according to the conventional program of teaching.To achieve objectives of the study, the researcher reformulated three lessons in Arabic language textbook in compliance with the reciprocal teaching strategy and prepared both the reflective thinking skills scale (reflection and observation, detecting fallacies, drawing conclusions, offering convincing explanations, and devising the recommended solutions) and the attitudes scale toward Arabic language. The validity and reliability for both research instruments were ensured.Results of the study exhibited a significant positive impact of utilizing the instructional program that is based on the reciprocal teaching strategy on developing the reflective thinking skills among third grade students in Arabic language subject, as well as on developing attitudes of students of the experimental group toward this subject.The study came out with a set of recommendations highlighting the need to devise such instructional programs in the Arabic language curricula that are based on the reciprocal teaching strategy.
Keywords: Reciprocal education strategy; reflective thinking skills; the trend towards Arabic language; third grade